It's a Wonderful Life - Capra, Frank, 1897-1991.; Bondi, Beulah, 1888-1981; Donna Reed; Frank Faylen; Henry Travers; Lionel Barrymore; Thomas Mitchell; James Stewart (USA Liberty Films, 1946)
George Bailey has so many problems he is thinking about ending it all - and it's Christmas ! As the angels discuss George, we see his life in flashback. As George is about to jump from a bridge, he ends up rescuing his guardian angel, Clarence. Clarence then shows George what his town would have looked like if it hadn't been for all his good deeds over the years. Will Clarence be able to convince George to return to his family and forget about suicide ?
An angel helps a compassionate but despairingly frustrated businessman by showing what life would had been like if he never existed.
Philip Van Doren Stern
Languages : English, French Subtitles : English, Turkish, French, Greek, Slovenian
Keywords: Fantasy; Romance; Drama